Worldly goods : a new history of the Renaissance - Jardine, Lisa (W. W. Norton, 1996)
"Fascinating . . . Jardine's attention to the material side of things is an important explanatory complement to the many histories of the period that have dwelt on the sublime works of art . . . Real history is in the details, the small stories, of which WORLDLY GOODS is a treasure house." Richard Bernstein, The New York Times